Stepping motors a guide to theory and practice - Acarnley, P. P. (Institution of Engineering and Technology, 2002)
The following topics are dealt with: Stepping motors; drive circuits; accurate load positioning: static torque characteristics; multistep operation: torque-speed characteristics; high-speed operation; open-loop control; closed-loop control; microprocessor-based stepping motor systems; appendix: pull-out torque-speed characteristics of bifilar-wound motors.